The Study of Eastern Judeo-Spanish - Schwarzwald, Ora Rodrigue (MiKAN, 2007)
This article focuses on the historical development of research relating to the language and culture of the eastern Judeo-Spanish communities that settled throughout the Ottoman Empire after their expulsion from Spain. Research into the linguistic, literary, musical, and folkloristic facets of the language began relatively late, compared with parallel research developments concerning other languages and communities. The study of canonical works preceded that of the folkloristic and oral ones. Hispanic interest in the language and its creativity began at the end of the 19th century and helped increase Jewish interest in the subject. Although it was initially the written documents that were catalogued, oral romances, cantigas, coplas (songs), and proverbs continue to be documented today. Researchers distinguish between literatures based on Hispanic sources and those based on original or “adapted” literatures from other cultures. The most studied written genres are Ladino translations of liturgical Hebrew texts and Me ‘am Lo ‘ez. It is the romances that dominate the study of oral literature. A highly important theoretical issue pertains to the era in which Judeo-Spanish became an independent language. This may have occurred either before the expulsion or later in the Diaspora, Other issues focus on the originality of the texts, dialectal differences, loan components, textual themes, musical and folkloristic traditions, etc. Most research issues follow the researchers’ individual interests. The study of Judeo-Spanish still lacks an interdisciplinary overview, but academic interest is increasing and several institutes teach and research both the language and its literature.